Influence of Organizational Culture on Enterprise Development: Selected Theoretical Aspects - Aneta MADYDA (Communications of International Proceedings, 2022)
This study presents the relationship between organizational culture and enterprise development. Organizational culture affects the functioning of enterprise. Creating the right organizational climate in the company allows employee to become aware participants of the company’s development. The integrity of the organizational culture with the tasks performed affects the productivity of employees.
Keywords: organizational culture; enterprise; development.